A rare new species of Leptohyphes Eaton (Ephemeroptera: Leptohyphidae) from the Lost World - Molineri, Carlos; Derka, Tomáš (Zootaxa, 2020)
A new species of Leptohyphes Eaton (Ephemerotera: Leptohyphidae) is described, diagnosed and illustrated from nymphs collected in the Pantepui region in Southeastern Venezuela. Leptohyphes kukenan sp. nov. is similar to Leptohyphes populus Allen because they share a unique character for the genus: male compound eyes are divided. Other unique characters for the new species include a plesiomorphic gill structure, with imbricated ventral lamellae, and paired subapical denticles on tarsal claw. The new species show a unique combination of characters that distinguish it from L. populus and all other species of Leptohyphes: fore and hind margin of femora with spines on strong elevated sockets, part of body and legs covered by small pale spots, tarsal claws with 4–5 marginal denticles and a subapical pair of submarginal denticles, pronotum with large rounded lateral projection, hind wing pads absent in female, gill formula 8/7/7/4/1, operculate gill with imbricated ventral lobes, and gill V without ventral extension on dorsal lamella.